Board monitoring, product market competition and firm performance. Issue 4 (2nd September 2019) - Singla, Monika; Singh, Shveta
Abstract : Purpose: This paper aims to analyze the monitoring role of board and product market competition in relation to firm performance. Further, this paper analyzes the moderating role of product market competition in influencing the board monitoring and firm value relationship in the context of an emerging economy, India. Design/methodology/approach: A large sample of 3, 854 firm-year observations has been used over a period of 10 years (2007-2016). Industry and year-fixed effect regression methodology has been used to test the hypothesized relationships. Findings: The empirical findings indicate that board monitoring adds negatively to the firm value. The results also indicate that product market competition bears an insignificant moderating effect on the effectiveness of board monitoring in India. However, a more in-depth analysis reveals that product market competition complements the weak board monitoring of business-group firms. Further, the effectiveness of the board monitoring (which is relatively stronger in business-group firms) is weakened by the increased level of product market competition for stand-alone firms. Research limitations/implications: A significant negative effect of board independence on the firm value raises the effectiveness of various policies advocating the board independence to strengthen the governance structure of the firms. The findings relating to the moderating role of product market competition for the business-group and stand-alone firms are helpful in understanding the governance behavior of the firms in relation to the external product market competition. Originality/value: External governance mechanisms such as the market for corporate control and product market competition have been described as significant corporate governance mechanisms. However, the empirical efficacy of these governance mechanisms has not been explored in a greater detail in the context of the emerging markets. This study aims to address this research gap.